The Influence of Consumer Characteristics on Insurance Product Purchase Decisions at Pan Pacific Insurance. PT – Medan - Ismail, Faruq Syauqi; Sulaiman, Najdi Nawri; Febrian, Habli Ridho; Sinulingga, Alexander Stefanus (Economic: Journal Economic and Business, 2024)
This research aims to analyze the influence of consumer characteristics on purchasing decisions for insurance products at PT Pan Pacific Insurance in Medan. This research uses a qualitative approach with descriptive research type. The data collection techniques used were in-depth interviews and observation. The research results show that consumer characteristics, both social and personal factors, have a significant influence on the decision to purchase insurance products at PT Pan Pacific Insurance in Medan. Social factors such as reference groups, family and social status are important considerations for consumers in choosing insurance products. Meanwhile, personal factors such as age, occupation, economic situation and lifestyle also influence consumer needs and preferences in choosing appropriate insurance products. The findings of this research can help PT Pan Pacific Insurance to develop more effective marketing strategies and adapt their insurance product offerings according to various consumer preferences and needs.